The influence of socioenvironmental risk factors on risk-taking behaviors among Bahamian adolescents: a structural equation modeling analysis - Elizabeth Schieber; Ava Wang; Grace Ou; Carly Herbert; Hoa T. Nguyen; Lynette Deveaux; Xiaoming Li (Health Psychology and Behavioral Medicine)
Background Adolescents’ risk-taking behaviors can have profound impacts on their future health. Few studies have established a relationship between multiple social environmental factors and adolescent risk behaviors. We used structural equation modeling to examine the role of parental monitoring and environmental risks on adolescents’ behavioral intentions and risk behaviors.Methods Data were collected through the baseline survey of a national implementation project among 2205 Grade 6 students in 24 government schools in The Bahamas in 2019. Structural equation modeling examined relations among parental monitoring, environmental risk factors, behavioral intentions, and risk behaviors.Results Students had engaged in various delinquent, substance use, and sexual risks. In the structural equation model, parental monitoring demonstrated direct negative (protective) effects on behavioral intentions and risk behaviors, whereas environmental risk factors had a direct positive effect on adolescent behavioral intentions and risk behaviors. The model had an R2 value of 0.57 for adolescent risk behaviors.Conclusion Parental monitoring and environmental risk factors had strong influences on risk-taking behaviors of early adolescents. Future adolescent health behavior interventions should consider offering additional prevention resources to early adolescents who are exposed to multiple environmental risk factors.